Integrating Oral Health Within Kenyan HIV Research & Policy Structure: Stakeholder Analysis - Ana Lucia Seminario; Marina Martinez; Immaculate Opondo; Sara Stanley; Matthew Saxton; Arthur M. Kemoli (Ubiquity Press, 2024)
Background: Kenya has a remarkably high burden of oral diseases, especially in vulnerable communities like persons with HIV (PWH). In the last few decades, the National AIDS & STI Control Programme has efficiently and successfully provided care and prevention against HIV for people living in Kenya. Objective: To assess the feasibility of integrating oral health into HIV research and policy structures in Kenya. Methods: The study took place between November 2021 and April 2022 in the cities of Nairobi, Kisumu, Mombasa, and Eldoret town. Using a semi-structured interview, three remote and 14 in-person sessions were conducted. Participants included individuals with professional experience in HIV and/or oral health such as researchers, potential mentors, institutional administrators, and other grant-funded experts. A qualitative analysis of recordings was performed by nine pretested independent reviewers, all with qualitative data analysis experience. Areas of interest included research, motivation, obstacles, and support. The free coding phase as well as an iterative grouping analysis (MIRO) was used. Findings: Of the 22 stakeholders interviewed in the study, researchers accounted for the majority (48%) of stakeholders, with the rest composed of practitioners (29%), university administrators (19%), and one public health administrator. University administrators were identified as having the most ability for resource mobilization followed by researchers and practitioners. All participants desired improved health outcomes using an evidence-based approach. The primary motivators were increased networks, collaborations, publications, and bridging the gap between oral health and HIV. While the obstacles to their desires included time and lack of funding, Institutional support through recruitment of qualified personnel, mentors, and mentees was their major desirable support. Conclusion: Stakeholders were unanimous in supporting integrating oral health within the current research and policy environment to address the gap between oral health and HIV, and to improve health outcomes through evidence-based interventions.